Strategy For Empowering Literature Community Of Dolok Still Through Street Library During The Covid-19 Pandemic - Uswatun Hasanah (International Journal of Cultural and Social Science, 2020)
This research discusses the empowerment of literacy in thecommunity through street library containers during the Covid19 pandemic in Dolok Masihul District. The purpose of thisresearch is to build reading interest for all people consideringthe condition of the Indonesian society's level of literacy is stillrelatively low. The method in this research is using descriptivequalitative method. The results showed that the level of literacyand reading interest in Dolok Masihul was still low, and thepublic was not very enthusiastic about the existence of this street library.